El autismo en la inclusión educativa de primero de básica de E.G.B de la unidad educativa “Dr. Gabriel García Moreno Guano” año lectivo (2020- 2021) - Padilla Pilco, Yadira Natali (2022)
The following investigation with the topic: "THE AUTISM IN THE EDUCATIONAL INCLUSION OF FIRST OF BASIC OF E.G.B OF THE EDUCATIONAL UNIT" DR. GABRIEL GARCÍA MORENO GUANO "YEAR 2020-2021", aims to analyze autism in educational inclusion, collect information on the theoretical foundations of Autism Spectrum Disorder in the basic elementary stage, identify the teaching-learning processes used by teachers in the classroom, to learn about the difficulties and potential that teachers have and to design a guide of pedagogical and treatment strategies that can be applied to students with autism of the first grade of the Educational Unit "Dr. Gabriel Garcia Moreno Guano", the framework The theory was carried out based on the two study variables with criteria from several authors, where (Vargas, 2012) mentions that autism is a generalized developmental disorder characterized by a qualitative alteration of social interaction. While (Lara, 2012) mentions that the history of ideas concerning autism has passed for a century by several periods that reflect the d Discussions around the nosography of disorders classified as autistic and their classification in the systems used successively. The applied methodology was through the observation guide to 21 children and a direct work with the autistic child ASD.